Spin excitations in solids from many-body perturbation theory - Friedrich, Christoph; Şaşıoğlu, Ersoy; Müller, Mathias; Schindlmayr, Arno; Blügel, Stefan (First Principles Approaches to Spectroscopic Properties of Complex Materials)
Collective spin excitations form a fundamental class of excitations in magnetic materials. As their energy reaches down to only a few meV, they are present at all temperatures and substantially influence the properties of magnetic systems. To study the spin excitations in solids from first principles, we have developed a computational scheme based on many-body perturbation theory within the full-potential linearized augmented plane-wave (FLAPW) method. The main quantity of interest is the dynamical transverse spin susceptibility or magnetic response function, from which magnetic excitations, including single-particle spin-flip Stoner excitations and collective spin-wave modes as well as their lifetimes, can be obtained. In order to describe spin waves we include appropriate vertex corrections in the form of a multiple-scattering T matrix, which describes the coupling of electrons and holes with different spins. The electron–hole interaction incorporates the screening of the many-body system within the random-phase approximation. To reduce the numerical cost in evaluating the four-point T matrix, we exploit a transformation to maximally localized Wannier functions that takes advantage of the short spatial range of electronic correlation in the partially filled d or f orbitals of magnetic materials. The theory and the implementation are discussed in detail. In particular, we show how the magnetic response function can be evaluated for arbitrary k points. This enables the calculation of smooth dispersion curves, allowing one to study fine details in the k dependence of the spin-wave spectra. We also demonstrate how spatial and time-reversal symmetry can be exploited to accelerate substantially the computation of the four-point quantities. As an illustration, we present spin-wave spectra and dispersions for the elementary ferromagnet bcc Fe, B2-type tetragonal FeCo, and CrO2 calculated with our scheme. The results are in good agreement with available experimental data.

The GW approximation for the electronic self-energy - Schindlmayr, Arno (Many-Electron Approaches in Physics, Chemistry and Mathematics)
Many-body perturbation theory is a well-established ab initio electronic-structure method based on Green functions. Although computationally more demanding than density functional theory, it has the distinct advantage that the exact expressions for all relevant observables, including the ground-state total energy, in terms of the Green function are known explicitly. The most important application, however, lies in the calculation of excited states, whose energies correspond directly to the poles of the Green function in the complex frequency plane. The accuracy of results obtained within this framework is only limited by the choice of the exchange-correlation self-energy, which must still be approximated in actual implementations. In this respect, the GW approximation has proved highly successful for systems governed by the Coulomb interaction. It yields band structures of solids, including the band gaps of semiconductors, as well as atomic and molecular ionization energies in very good quantitative agreement with experimental photoemission data.

Theoretical investigation of the band structure of picene single crystals within the GW approximation - Yanagisawa, Susumu; Morikawa, Yoshitada; Schindlmayr, Arno (Japanese Journal of Applied Physics)
We investigate the band dispersion and related electronic properties of picene single crystals within the GW approximation for the electronic self-energy. The width of the upper highest occupied molecular orbital (HOMOu) band along the Γ–Y direction, corresponding to the b crystal axis in real space along which the molecules are stacked, is determined to be 0.60 eV and thus 0.11 eV larger than the value obtained from density-functional theory. As in our recent study of rubrene using the same methodology [S. Yanagisawa, Y. Morikawa, and A. Schindlmayr, Phys. Rev. B 88, 115438 (2013)], this increase in the bandwidth is due to the strong variation of the GW self-energy correction across the Brillouin zone, which in turn reflects the increasing hybridization of the HOMOu states of neighboring picene molecules from Γ to Y. In contrast, the width of the lower HOMO (HOMOl) band along Γ–Y remains almost unchanged, consistent with the fact that the HOMOl(Γ) and HOMOl(Y) states exhibit the same degree of hybridization, so that the nodal structure of the wave functions and the matrix elements of the self-energy correction are very similar.

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computing Solids: Models, ab initio Methods and Supercomputing)

Interaction of a classical laser field with a model Rydberg atom in a mixed state prepared by entanglement with few-photon quantum light - Sharapova, Polina; Tikhonova, O V (Journal of Physics: Conference Series)
Keywords: General Physics and Astronomy

Bright squeezed-vacuum source with 11 spatial mode - Pérez, A. M.; Iskhakov, T. Sh.; Sharapova, Polina; Lemieux, S.; Tikhonova, O. V.; Chekhova, M. V.; Leuchs, G. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Sub-cycle control of terahertz high-harmonic generation by dynamical Bloch oscillations - Meier, Torsten; Schubert, O.; Hohenleutner, M.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S. W.; Huber, R. (Nature Photonics)
Ultrafast charge transport in strongly biased semiconductors is at the heart of high-speed electronics, electro-optics and fundamental solid-state physics1,2,3,4,5,6,7,8,9,10,11,12,13. Intense light pulses in the terahertz spectral range have opened fascinating vistas14,15,16,17,18,19,20,21. Because terahertz photon energies are far below typical electronic interband resonances, a stable electromagnetic waveform may serve as a precisely adjustable bias5,11,17,19. Novel quantum phenomena have been anticipated for terahertz amplitudes, reaching atomic field strengths8,9,10. We exploit controlled (multi-)terahertz waveforms with peak fields of 72 MV cm−1 to drive coherent interband polarization combined with dynamical Bloch oscillations in semiconducting gallium selenide. These dynamics entail the emission of phase-stable high-harmonic transients, covering the entire terahertz-to-visible spectral domain between 0.1 and 675 THz. Quantum interference of different ionization paths of accelerated charge carriers is controlled via the waveform of the driving field and explained by a quantum theory of inter- and intraband dynamics. Our results pave the way towards all-coherent terahertz-rate electronics.

Adiabatic tracking of quantum many-body dynamics - Saberi, H.; Opatrný, T.; Mølmer, K.; del Campo,, A. (Physical Review A)
The nonadiabatic dynamics of a many-body system driven through a quantum critical point can be controlled using counterdiabatic driving, where the formation of excitations is suppressed by assisting the dynamics with auxiliary multiple-body nonlocal interactions. We propose an alternative scheme which circumvents practical challenges to realize shortcuts to adiabaticity in mesoscopic systems by tailoring the functional form of the auxiliary counterdiabatic interactions. A driving scheme resorting in short-range few-body interactions is shown to generate an effectively adiabatic dynamics.

Vibrational Fingerprints of LiNbO3-LiTaO3Mixed Crystals - Sanna, Simone; Riefer, A.; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Rüsing, Michael; Widhalm, A.; Zrenner, Artur (Ferroelectrics)
Atomistic simulations in the framework of the density functional theory have been used to model morphologic and vibrational properties of lithium niobate–lithium tantalate mixed crystals as a function of the [Nb]/[Ta] ratio. Structural parameters such as the crystal volume and the lattice parameters a and c vary roughly linearly from LiTaO3 to LiNbO3, showing only minor deviations from the Vegard behavior. Our ab initio calculations demonstrate that the TO1, TO2 and TO4 vibrational modes become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. Furthermore, the investigated zone center A1 -TO phonon modes are characterized by a pronounced stoichiometry dependence. Frequency shifts as large as 30 cm−1 are expected as the [Nb]/[Ta] ratio grows from 0 to 1. Therefore, spectroscopic techniques sensitive to the A1 modes (such as Raman spectroscopy), can be employed for a direct and non-destructive determination of the crystal composition.
Keywords: Ferroelectrics; vibrational properties; LiNbO3; LiTaO3; mixed crystals

Transition energies and direct-indirect band gap crossing in zinc-blende AlxGa1−xN - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schupp, Thorsten; As, Donat J.; Feneberg, Martin; Goldhahn, Rüdiger (Physical Review B)

Newton's cradles in optics: From N-soliton fission to soliton chains - Driben, R.; Malomed, B.A.; Yulin, A. V.; Skryabin, D.V. (Physical Review A)
A mechanism for creating a Newton's cradle (NC) in nonlinear light wave trains under the action of the third-order dispersion (TOD) is demonstrated. The formation of the NC structure plays an important role in the process of fission of higher-order (N) solitons in optical fibers. After the splitting of the initial N soliton into a nonuniform chain of fundamental quasisolitons, the tallest one travels along the entire chain, through consecutive collisions with other solitons, and then escapes, while the remaining chain of pulses stays as a bound state, due to the radiation-mediated interaction between them. Increasing the initial soliton's order, N, leads to the transmission through, and release of additional solitons with enhanced power, along with the emission of radiation, which may demonstrate a broadband supercontinuum spectrum. The NC dynamical regime remains robust in the presence of extra perturbations, such as the Raman and self-steepening effects, and dispersion terms above the third order. It is demonstrated that essentially the same NC mechanism is induced by the TOD in finite segments of periodic wave trains (in particular, soliton chains). A difference from the mechanical NC is that the TOD-driven pulse passing through the soliton array collects energy and momentum from other solitons. Thus, uniform and nonuniform arrays of nonlinear wave pulses offer an essential extension of the mechanical NC, in which the quasiparticles, unlike mechanical beads, interact inelastically, exchanging energy and generating radiation. Nevertheless, the characteristic phenomenology of NC chains may be clearly identified in these nonlinear-wave settings too.

Instabilities, solitons and rogue waves in PT-coupled nonlinear waveguides - Bludov, Y.V.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Journal of Optics)
We considered the modulational instability of continuous-wave backgrounds, and the related generation and evolution of deterministic rogue waves in the recently introduced parity–time (P T)-symmetric system of linearly coupled nonlinear Schrödinger equations, which describes a Kerr-nonlinear optical coupler with mutually balanced gain and loss in its cores. Besides the linear coupling, the overlapping cores are coupled through the cross-phase-modulation term too. While the rogue waves, built according to the pattern of the Peregrine soliton, are (quite naturally) unstable, we demonstrate that the focusing cross-phase-modulation interaction results in their partial stabilization. For P T-symmetric and antisymmetric bright solitons, the stability region is found too, in an exact analytical form, and verified by means of direct simulations

Generation of tightly compressed solitons with a tunable frequency shift in Raman-free fibers - Driben, R.; Malomed, B.A. (Optics Letters)
Optimization of the compression of input 𝑁 -solitons into robust ultra-narrow fundamental solitons, with a tunable up- or downshifted frequency, is proposed in photonic crystal fibers free of the Raman effect. Due to the absence of the Raman self-frequency shift, these fundamental solitons continue propagation, maintaining the acquired frequency, once separated from the input 𝑁 soliton’s temporal slot. A universal optimal value of the relative strength of the third-order dispersion is found, providing the strongest compression of the fundamental soliton is found. It depends only on the order of the injected 𝑁 -soliton. The largest compression degree significantly exceeds the analytical prediction supplied by the Satsuma–Yajima formula. The mechanism behind this effect, which remains valid in the presence of the self-steepening, is explained.

Trapping of light in solitonic cavities and its role in the supercontinuum generation - Driben, R.; Yulin, A. V.; Efimov, A.; Malomed, B.A. (Optics Express)
We demonstrate that the fission of higher-order N-solitons with a subsequent ejection of fundamental quasi-solitons creates cavities formed by a pair of solitary waves with dispersive light trapped between them. As a result of multiple reflections of the trapped light from the bounding solitons which act as mirrors, they bend their trajectories and collide. In the spectral domain, the two solitons receive blue and red wavelength shifts, and the spectrum of the trapped light alters as well. This phenomenon strongly affects spectral characteristics of the generated supercontinuum. Consideration of the system's parameters which affect the creation of the cavity reveals possibilities of predicting and controlling soliton-soliton collisions induced by multiple reflections of the trapped light.

Inversion and tight focusing of Airy pulses under the action of third-order dispersion - Driben, R.; Hu, Y.; Chen, Z.; Malomed, B.A.; Morandotti, R. (Optics Letters)
By means of direct simulations and theoretical analysis, we study the nonlinear propagation of truncated Airy pulses in an optical fiber exhibiting both anomalous second-order and strong positive third-order dispersions (TOD). It is found that the Airy pulse first reaches a finite-size focal area as determined by the relative strength of the two dispersion terms, and then undergoes an inversion transformation such that it continues to travel with an opposite acceleration. The system notably features tight focusing if the TOD is a dominant factor. These effects are partially reduced by Kerr nonlinearity.

Nonlinear modes in binary bosonic condensates with pseudo–spin-orbital coupling - Zezyulin, D.A.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Physical Review A)
We consider an effectively one-dimensional binary Bose-Einstein condensate (BEC) with nonlinear repulsive interactions and linear spin-orbit (SO) and Zeeman-splitting couplings. In the presence of the trapping harmonic-oscillator (HO) potential, we report the existence of even, odd, and asymmetric spatial modes. They feature alternating domains with opposite directions of the pseudospin, i.e., antiferromagnetic structures, which is explained by the interplay of the linear couplings, HO confinement, and repulsive self-interaction. The number of the domains is determined by the strength of the SO coupling. The modes are constructed analytically in the weakly nonlinear system. The dynamical stability of the modes is investigated by means of the Bogoliubov–de Gennes equations and direct simulations. A notable result is that the multi-domain-wall (DW) structures are stable, alternating between odd and even shapes, while the simplest single-DW structure is unstable. Thus, the system features a transition to the complex ground states under the action of the SO coupling. The addition of the Zeeman splitting transforms the odd modes into asymmetric ones via spontaneous symmetry breaking. The results suggest possibilities for switching the binary system between states with opposite (pseudo)magnetization by external fields, and realization of similar stable states and dynamical effects in solid-state and nonlinear-optical settings emulated by the SO-coupled BECs.

Soliton interaction mediated by cascaded four wave mixing with dispersive waves - Yulin, A. V.; Driben, R.; Malomed, B.A.; Skryabin, D.V. (Optics Express)
We demonstrate that trapping of dispersive waves between two optical solitons takes place when resonant scattering of the waves on the solitons leads to nearly perfect reflections. The momentum transfer from the radiation to solitons results in their mutual attraction and a subsequent collision. The spectrum of the trapped radiation can either expand or shrink in the course of the propagation, which is controlled by arranging either collision or separation of the solitons.

Collective effects in second-harmonic generation from split-ring-resonator arrays - Niesler, Fabian B.; Linden, Stefan; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, Martin (Conference on Lasers and Electro-Optics 2012)
We perform experiments on resonant second-harmonic generation from planar gold split-ring-resonator arrays under normal incidence of light as a function of the lattice constant. Optimum nonlinear conversion occurs at intermediate lattice constants.
Keywords: tet_topic_shg; tet_topic_meta

Optimal second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVII)
Previous experimental measurements and numerical simulations give evidence of strong electric and magnetic field interaction between split-ring resonators in dense arrays. One can expect that such interactions have an influence on the second harmonic generation. We apply the Discontinuous Galerkin Time Domain method and the hydrodynamic Maxwell-Vlasov model to simulate the linear and nonlinear optical response from SRR arrays. The simulations show that dense placement of the constituent building blocks appears not always optimal and collective effects can lead to a significant suppression of the near fields at the fundamental frequency and, consequently, to the decrease of the SHG intensity. We demonstrate also the great role of the symmetry degree of the array layout which results in the variation of the SHG efficiency in range of two orders of magnitude.
Keywords: tet_topic_shg; tet_topic_meta

Geometrical and optical benchmarking of copper guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory† - Jesser, Anton; Rohrmüller, Martin; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)